Cumplimiento de los indicadores de calidad en la unidad de cuidados intensivos del hospital Manuel Ygnacio Monteros, Loja - Arias Quizhpe, Fernando José (2023)
Compliance with quality indicators in different health institutions is essential to avoid damage, errors and reduce the risk to users when receiving health care. Therefore, the present study was proposed with the objective of evaluating compliance with quality indicators in the Intensive Care Unit of the Manuel Ygnacio Monteros General Hospital in Loja. A non-experimental-observational study was carried out with a quantitative, descriptive and cross-sectional approach. In addition, the documentary review technique was used in clinical histories, databases and hospital records together with direct observation. To collect the information, an instrument was used which was characterized by having two sections, the first reflects the characterization of the Intensive Care Unit, in which the nursing professionals who work and the infrastructure of the service are considered; as a second point, compliance with safe practices is evaluated. The results showed the existence of 24 nursing professionals, which implies a predominance in comparison with the rest of the health professionals. In relation to the safe administrative practices, the service reaches the optimal standard percentage of compliance, in contrast to the safe care practices where an optimal standard of compliance is not achieved, mainly due to the lack of adherence in the practices of correct administration of medications and the prevention of pressure ulcers, as well as in the administrative-care practices, in the prevention of falls and hand hygiene. In conclusion, in the Intensive Care Unit, most of the safe practices fail to reach an optimal percentage of compliance